Farmer's stance on decreasing production of local red onion (Allium cepa L.) farming in Buttu Pamboang Village, Majene - Maswad, Maswad; Beddu, Mir Alam; Karim, Ikawati; Putri, Dwi Ahrisa; Suyono, Suyono (Anjoro: International Journal of Agriculture and Business, 2020)
In general, farmers in Buttu Pamboang Village in Majene District in carrying out the cultivation of onion plants have not applied the rules of cultivation correctly and precisely, resulting in a decline in crop. Agricultural commodities have a strategic role in realizing government policy to increase foreign exchange acquisition. The toughness of the role in the world trade globalization era is faced with the competition of commodity quality, both in domestic and foreign markets. This Era is characterized by the increasingly free commodity trading between countries in the world including vegetable commodities. In Indonesia, the local red onion plant (Allium cepa L.) has been cultivated by farmers as a commercial farming. However, the presence and demand of red onion that continue to increase every year cannot be followed by the increase in production. Data of the Agricultural office of Pamboang Village, October 2015 that the amount of local red onion productivity ranged from 5-6 tons and the production amount ranged from 10-12 tons with 2 ha of farmland area in 2014. It can be concluded that the production of local red onion in 2015 in the Pamboang Village decreased compared to the previous year, the red onion productivity of 2015 average ranged from 2-3 tons. This research aims to identify the attitude of farmers in Buttu Pamboang Village to decline in production in the onion farming business and know the factors that cause a decline in the production of local red onion in Buttu Pamboang Village in Pamboang District of Majene Regency. To identify the assessment of the farmer's stance, analyzed using Likert scale. The Likert scale is the identification of assessments to measure the attitudes and opinions and perceptions of the person/group on social symptoms. The results of the study proved that the attitude of farmers in Buttu Pamboang Village to the decline of production is good or well received.